Physicochemical Properties and in vitro Digestibility of Myofibrillar Proteins From the Scallop Mantle (Patinopecten yessoensis) Based on Ultrahigh Pressure Treatment - Liu, Xiaohan; Mao, Kemin; Sang, Yaxin; Tian, Guifang; Ding, Qiuyue; Deng, Wenyi (Frontiers in Nutrition, 2022)
The utilization of myofibrillar proteins (MP) from scallop mantle was limited due to its poor digestibility in vitro. In this study, structural properties and in vitro digestibility of MP were evaluated after modified by ultra-high pressure (UHP) at different pressures (0.1, 100, 200, 300, 400 and 500 MPa). The results showed that high pressure could significantly increase the ordered structure content like α-helix, inhibit the formation of disulfide bonds, and decrease surface hydrophobicity. Moreover, MP possessed the optimal solubility and in vitro digestibility properties at 200 MPa due to the minimum particle size and turbidity, relatively dense and uniform microstructure. The results indicated that UHP-treatment was an effective method to improve the digestibility of MP from scallop mantle and lay a theoretical basis for the functional foods development of poor digestion people and comprehensive utilization of scallop mantles.